Market Power in Bilateral Oligopoly Markets with Nonexpandable Infrastructures - Yukihiko Funaki; Harold Houba; Evgenia Motchenkova (Tinbergen Institute, 2012)
We consider price-fee competition in bilateral oligopolies with perfectly-divisible goods, non-expandable infrastructures, concentrated agents on both sides, and constant marginal costs. We define and characterize stable market outcomes. Buyers exclusively trade with the supplier with whom they achieve maximal bilateral joint welfare. Prices equal marginal costs. Threats to switch suppliers set maximal fees. These also arise from a negotiation model that extends price competition. Competition in both prices and fees necessarily emerges. It improves welfare compared to price competition, but consumer surpluses do not increase. The minimal infrastructure achieving maximal aggregate welfare differs from the one that protects buyers most.
Keywords: C78; L10; L14; D43; R10; 330; Assignment Games; Infrastructure; Negotiations; Non-linear pricing; Market Power; Countervailing power